Heart rate variability in athletes: relationship with central and peripheral performance - Hedelin, R.; Bjerle, P.; Henriksson-Larsen, K. (Medicine & Science in Sports & Exercise, 2001)
PURPOSE: To investigate relationships between heart rate variability (HRV) and peripheral and central performance measures, 17 cross-country (X-C) skiers and seven canoeists were studied before and after a training period of 7 months. METHODS: For the skiers and canoeists respectively, leg and arm peak torque (Tq), time to peak torque (TiTq), and total work (Wrk) were measured in an isokinetic dynamometer. Maximal oxygen uptakes (VO2max) were obtained from treadmill tests. Power spectral analysis of HRV was performed on electrocardiographic recordings in the resting supine position and after a tilt to yield power in the low-frequency (0.04-0.15 Hz) and high-frequency (0.15-0.45 Hz) components of HRV. RESULTS: The change in normalized LF-variability in standing (DeltaLFnT) correlated (P < 0.01) with the changes in TiTq (r = 0.63), max lactate (r = -0.63), and VO2max (r = -0.53). The change in absolute LFT was inversely correlated with the change in Tq. Subjects who improved VO2max were characterized by consistently higher high-frequency and total HRV than subjects with deteriorated aerobic capacity (P < 0.05). CONCLUSION: The results suggest that improved measures of both peripheral and central (aerobic) work capacities were associated with a reduction of low-frequency HRV in the tilted position. High-frequency and total HRV did not change in proportion with changes in muscle performance or aerobic capacity, but the ability to further improve VO2max with training in these already fit subjects seemed to depend on their average levels of these HRV measures, interpreted to reflect parasympathetic activity.